Methodological aspects of national surveys in Brazil: contributions to the debate on oral health surveillance - Andrea Maria Duarte VARGAS; Doralice Severo da Cruz TEIXEIRA; Maria Cecília Goi Porto ALVES; Gizelton Pereira ALENCAR; Regina Tomie Ivata BERNAL; Mara VASCONCELOS; Rafaela da Silveira PINTO; Andreia Maria Araújo DRUMMOND; Rosa Núbia Vieira de MOURA; Viviane Elisângela GOMES; Raquel Conceição FERREIRA (Brazilian Oral Research)
Abstract This study analyzes the methodological aspects of the SB Brasil epidemiological surveys conducted in 2003, 2010, and 2023. The sample plan, fieldwork, sampling process, investigated variables, and operational aspects were examined based on technical documents and relevant publications. All three surveys adopted complex, probabilistic cluster sampling, with different study domains and sample sizes across editions. Data collection was conducted by SUS workers in all three editions, and Community Health Agents (ACS) were included as data collector in 2023. In this edition, the listing process occurred in a separate phase before the interview and examination, in two stages, to update the address list and identify eligible residents. Data collection included oral examinations and household interviews. The health conditions and oral health indices, as well as the criteria for defining the assessed conditions for each age group, remained similar across surveys. SB Brasil 2023 introduced, for the first time, the evaluation of the clinical consequences of untreated dental caries and the intervention urgency. There was an expansion of demographic and socioeconomic variables and subjective aspects of oral health over the editions. Increasing incorporation of technologies for data recording was observed, with automation of the sample selection process and report generation to support fieldwork monitoring. These changes reflect a continuous commitment to producing high-quality data, essential for supporting public policies and strengthening oral health surveillance in Brazil.